From Preoperative Imaging to Postoperative Rehabilitation: The Essential Roles of Radiology Technologists, Nursing Specialists, Physical therapist, and Operation Room Technicians - Khalid Ali Al Kalquefly; Safiah Mohammed Hakami; Durayqi Mousa Ibrahim Ageeli; Majed Abdullah Alshammari; Salha Hamod Mashiakhy; Nourah Saleh Al Khaibari; Tumadir Mohamad Al Hawsah; Samar Muhaysin Ayed Alharthi; Rawan Faisal Saeed Almuwallad; Deema Fahad Mastour AlMutairi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Patients undergoing surgery require an integrated and multidisciplinary approach in the line of management, where different cadres of healthcare providers work in a team toward optimum outcomes. In modern surgical practice, radiology technologists, specialist nurses, physical therapists, and operation room technicians make indispensable contributions along the continuum of care, right from preoperative imaging to postoperative rehabilitation. The radiology technologists help by providing the medical doctor with a well-articulated diagnostic image that aids in the exact planning and performance of the surgery, ensuring that the surgical team is passing the right information so as to avoid complications. Operating room technicians make sure that the operating environment is sterile and that all surgical instruments are prepared, correctly functioning, and thus support the surgical team in maintaining efficiency and safety for the patient during the procedure. The nursing professionals take center stage in the postoperative period by ensuring pain is under control, infection does not occur, and vital signs are constantly monitored to detect any early complication symptoms. Besides, they offer psychological services-emotional support to the patients. A physical therapist enhances recovery with an individualized rehabilitation program that focuses on restoration of mobility, strength, and functionality. This is important in restoring the activity level of the patient to normal as fast and safely as possible. Their interventions are vital in the reduction of long-term disability and physical dependence, and the improvement of the quality of life in general. Ultimately, the success of the surgical process and the speed at which recovery will be realized rest completely on the expertise, coordination, and teamwork among these professionals. Each has his special skill and knowledge that, when combined, offers optimal patient care and holistic approaches both to the surgeries and rehabilitation. Thus, teamwork in coordination basically forms the foundation of any successful surgical management and recovery of a patient; hence, their combined effort is vital to achieve favorable results in modern health systems.